Co-production of Hydrogen and Ethanol of Escherichia coli SS1 Isolate - Chiu-Shyan Soo (Science Faculty of Chiang Mai University, 2019)
Simultaneous production of hydrogen and ethanol from waste materials has potential for the development of a more cost-effective biofuels generation process. This study aimed to conduct glycerol fermentation using Escherichia coli SS1 to establish its hydrogen and ethanol co-production profile. Anaerobic fermentation was performed at 37°C with different concentrations of glycerol as a substrate. E. coli SS1 had exponential growth within 24 h (OD600 of 1.6), and hydrogen and ethanol were produced in abundance within 48 h of fermentation. Fermentation using 10 g/l of glycerol achieved the highest yield, 0.57 mol of hydrogen and 0.88 mol of ethanol per mol of glycerol. The highest hydrogen productivity (1.85 mmol/l/h) and ethanol productivity (3.13 mmol/l/h) were obtained at 45 g/l of glycerol. This report provides the complete data set for hydrogen and ethanol co-production yield and productivity by the wild-type E. coli SS1 and serves as a useful reference for other researchers working on the co-production of hydrogen and ethanol.